ChemInform Abstract: Color‐Tunable Photoluminescence and Energy Transfer Properties of Single‐Phase Ba10(PO4)6O:Eu2+, Mn2+ Phosphors. Issue 1 (17th December 2015) - Guo, Qingfeng; Liao, Libing; Mei, Lefu; Liu, Haikun
Abstract: Single‐phase Ba10‐x‐y (PO4 )6 O:xEu 2+, yMn 2+ phosphors are prepared by solid state reaction of stoichiometric mixtures of BaCO3, NH4 H2 PO4, Eu2 O3, and MnCO3 (alumina crucibles, flowing 10% H2 /90% N2, 1200 °C, 5 h).